COMPARATIVE ANALYSIS AND ASSESSMENT OF THE LEVEL OF DIGITALIZATION OF ARMENIAN AND RUSSIAN ORGANIZATIONS BY TYPES OF ECONOMIC ACTIVITY - Tatul M. Mkrtchyan; Manuk E. Movsisyan; Lusine V. Karapetyan; Tatevik G. Vardanyan (Proceedings on Engineering Sciences)
The research aims to study the level of digitalization of organizations in the Republic of Armenia and the Russian Federation according to the types of their economic activity, conduct their comparative analysis, assess their digital level, revealing the more developed stages of digitalization of Armenian and Russian organizations, and calculate their business digitalization index. Considering the aim of this research, the authors applied comparative analysis, general scientific analysis, grouping, and generalization. Thus, the research results show that Armenian and Russian organizations have a relatively high level of primary computerization. The differences in the second and third levels of digitalization between the two countries are relatively minor. However, at the top level of the digitalization pyramid, the gap is widening, highlighting Russia’s dominance in organizational digitalization.